New Oppiidae (Acari, Oribatida) from New Zealand - Ermilov, Sergey G.; Minor, Maria A. (Zootaxa, 2015)
Three new species of oribatid mites of the family Oppiidae (Oribatida, Oppioidea), belonging to the genera/subgenera Tripiloppia Hammer, 1968 and Lanceoppia (Baioppia) Luxton, 1985, are described from Central Otago, South Island, New Zealand. Tripiloppia frigida sp. nov. is morphologically similar to T. dalenii Hammer, 1968, but differs from the latter by the lanceolate bothridial setae, five pairs of genital setae, and trapezoid anterior notogastral protrusion. Tripiloppia alpina sp. nov. is morphologically similar to T. frigida sp. nov., but differs from the latter by the short, diagonal costulae, strong teeth in humeral regions, barbed lamellar setae, and interlamellar setae shorter than rostral setae. Lanceoppia (Baioppia) trapezoides sp. nov. is morphologically similar to L. (B.) moritzi Hammer, 1968, but differs from the latter by the larger body length, presence of notogastral setae c, and long interlamellar setae. The taxonomic status of the genus Autoppia Golosova & Karppinen, 1983 and systematic placement of Autoppia algicola Golosova & Karppinen, 1983 are discussed, resulting in the following taxonomic proposals: Tripiloppia Hammer, 1968 (=Autoppia Golosova & Karppinen, 1983 syn. nov.); Tripiloppia algicola (Golosova & Karppinen, 1983) comb. nov. The identification keys to known species of Tripiloppia and Lanceoppia (Baioppia) are given.